Physics with trapped charged particles : lectures from the Les Houches Winter School (Imperial College Press, 2014)
This book is a collection of articles on Physics with Trapped Charged Particles by speakers at the Les Houches Winter School. The articles cover all types of physics with charged particles, and are aimed at introducing the basic issues at hand, as well as the latest developments in the field. It is appropriate for PhD students and early career researchers, or interested parties new to the area.